ENVIRONMENTALLY FRIENDLY, CARDBOARD-BASED BLISTER PACKAGING - FAZEKAS, Attila (2025)
The subject of the invention relates to environmentally friendly, cardboard-based blister packaging, furthermore to a blister card that may be used for blister packaging, and to a method for the production of the blister card, in the case of which the blister card (1) may be removed from the blister film (2) without residue, and as a result of this the paper and plastic components of the packaging may be selectively collected. An important feature of the solutions according to the invention is that with the method for the production of the blister card (1) a novel unique layer order is created as a result of which the blister card (1) and the blister film (2) do not come into contact with each other in any way whatsoever, and this makes it possible to separate the two types of material without contamination, and without tearing up any fibres. L'objet de l'invention concerne un emballage-coque à base de carton respectueux de l'environnement, en outre une carte-coque qui peut être utilisée pour un emballage-coque, et un procédé de production de la carte-coque, dans le cas où la carte-coque (1) peut être retirée du film-coque (2) sans résidu, ce qui permet de collecter sélectivement les composants papier et plastique de l'emballage. Une caractéristique importante des solutions selon l'invention est qu'avec le procédé de fabrication de la carte-coque (1), un nouvel ordre de couche unique est créé grâce auquel la carte-coque (1) et le film-coque (2) n'entrent pas en contact l'un avec l'autre de quelque manière que ce soit, ce qui permet de séparer les deux types de matériau sans contamination, et sans déchirement de fibres.